DESAIN PEMBELAJARAN MATEMATIKA DENGAN KONTEKS PERMAINAN KULI BIA PADA MATERI FAKTOR PERSEKUTUAN TERBESAR DAN KELIPATAN PERSEKUTUAN TERKECIL - Emy Sohilait; Yahya Lamasano (Universitas Muhammadiyah Semarang, 2020)
The learning process of the concept of greatest and Least which are the prerequisites of the greatest common divisor and the least common multiple in class IV SD Inpres 2 Waipo is carried out with the teaching paradigm that is, using T tables, multiples, and not using student thought conjectors in find concepts or material. This underlies researchers to design learning designs using Realistic Mathematics Education (RME) with the context of the kuli bia game as a starting point. The purpose of this study is to produce a learning trajectory and determine the impact of the use of learning designs on the mathematical knowledge construction process. Design research was chosen to achieve this goal which consists of three stages: preliminary design, teaching experiment, retrospective analysis. The results of the study found that the kuli bia game provides an important role in supporting learning and increases learning motivation, able to understand the material based on the learning trajectories generated, provides a variety of strategies in solving problems both at the situational stage, models of, models for and formal stages, the implementation of RME with the context of the kuli bia game on the material is running optimally, the response of students and teachers is positive and effective management of learning in the classroom.